2020
DOI: 10.1038/s41598-020-67148-6
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy vs Quantitative Polymerase Chain Reaction In Early Stage Huanglongbing Diagnostics

Abstract: Raman spectroscopy (RS) is an emerging analytical technique that can be used to develop and deploy precision agriculture. RS allows for confirmatory diagnostic of biotic and abiotic stresses on plants. Specifically, RS can be used for Huanglongbing (HLB) diagnostics on both orange and grapefruit trees, as well as detection and identification of various fungal and viral diseases. The questions that remain to be answered is how early can RS detect and identify the disease and whether RS is more sensitive than qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Partial least squares discriminant analysis (PLS-DA) was performed to differentiate between the experimental classes and identify spectral regions that best explained separation between the classes. Our own experimental results, as well as findings reported by other groups, show that PLS-DA performs equally well or better than other chemometric methods, such as linear discriminant analysis (LDA) or soft independent modeling by class analogy (SIMCA) (Farber et al, 2021;Lee et al, 2018;Sanchez, Pant, Irey, et al, 2019;Sanchez, Pant, Mandadi, & Kurouski, 2020;Shashilov & Lednev, 2010). Therefore, we have selected PLS-DA for statistical analysis of spectra collected in this study.…”
Section: Multivariate Data Analysismentioning
confidence: 61%
“…Partial least squares discriminant analysis (PLS-DA) was performed to differentiate between the experimental classes and identify spectral regions that best explained separation between the classes. Our own experimental results, as well as findings reported by other groups, show that PLS-DA performs equally well or better than other chemometric methods, such as linear discriminant analysis (LDA) or soft independent modeling by class analogy (SIMCA) (Farber et al, 2021;Lee et al, 2018;Sanchez, Pant, Irey, et al, 2019;Sanchez, Pant, Mandadi, & Kurouski, 2020;Shashilov & Lednev, 2010). Therefore, we have selected PLS-DA for statistical analysis of spectra collected in this study.…”
Section: Multivariate Data Analysismentioning
confidence: 61%
“…Therefore, a quick, non-invasive, portable, and confirmatory approach for diagnostics of viral disease is strongly desired. We have previously shown that Raman spectroscopy (RS) can be used to detect and identify plant diseases caused by fungi, viruses, and bacteria (Farber and Kurouski, 2018;Farber et al, 2019;Sanchez et al, 2020). This is highly important for agriculture because RS is non-invasive, non-destructive, and typically requires little-to-no sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we demonstrated that, by using RS, HLB can be distinguished from nutrient deficiency and secondary diseases such as blight ( Sanchez et al, 2019b ). Our recent findings show that RS is far more sensitive than qPCR, the golden standard in pathogen diagnostics ( Sanchez et al, 2020d ). Further elucidation of biochemical origin of RS-detected metabolite changes will further expand its utility in digital faming.…”
Section: Introductionmentioning
confidence: 99%